Anti-quorum sensing properties of melicope lunu-ankenda, piper betle, gnetum gnemon and piper nigrum / Tan Li Ying - Tan, Li Ying (2013)

(untitled)
Quorum sensing (QS) is a communication tool of bacteria that is involved in the regulation of bacterial virulence determinants, therefore making it an interesting target to attenuate pathogens. In this study, the anti-QS activities of four Malaysia‟s edible, local plants, namely, Melicopelunu-ankenda, Piper betle, Gnetumgnemon and Piper nigrum were explored by testing the hexane, chloroform and methanol extracts of the plants on Chromobacteriumviolaceum CV026, Escherichia coli [pSB401], E. coli [pSB1075],Pseudomonas aeruginosa PA01 and P. aeruginosaPA01lecA::lux. Qualitative studies of violacein inhibition of C. violaceum CV026 showed that most of the extracts except for the methanol extract of P. betle and chloroform and methanol extracts of G. gnemoninhibited the violacein productionin the presence of QS signals. On the other hand, quantitation assay on the violacein produced by C. violaceum CV026 showed that M. lunu-ankenda chloroform and methanol extracts, all three extracts of P. betle and P. nigrum significantly inhibited the violacein synthesis. In the presence of QS signals, bioluminescence produced by E. coli [pSB401] was inhibited by all of the extracts while only P. betle hexane extract, G. gnemon chloroform and methanol extracts inhibited bioluminescence of E. coli [pSB1075]. All three extracts of M. lunu-ankenda and P. betle as well as chloroform extract of G. gnemon inhibited pyocyanin synthesis of P. aeruginosaPA01. lecA expression was significantly disrupted by the chloroform extracts of both G. gnemon and P. betle as well as the methanol extracts of P. betle. Swarming motility of P. aeruginosa PA01 was inhibited by the extracts of M. lunu-ankenda (chloroform) and P. betle (methanol). Fractionation of chloroform extract of M. lunu-ankenda leads to a total of 14 fractions. These 14 fractions were then tested on E. 4 coli [pSB401], P. aeruginosaPA01lecA::lux and swarming motility of P. aeruginosa PA01. None of the fractions exhibited inhibition against lecAexpression. Fraction 4 and Fraction 11-14 showed inhibition against bioluminescence synthesis by E. coli [pSB401] while for swarming motility assay, only Fraction 5 and Fraction 11 showed observable inhibition. At this point of time, although the chemical nature of the anti-QS compounds from M. lunu-ankenda, P. betle,G. gnemon and P. nigrum are currently unknown, this study proves that local Malaysian plants could serve as leads in the search for anti-QS compounds.